Manual de contabilidade para condomínios: uma abordagem prática - Figueiredo, Danilo Prado (2024)
Condominiums are entities with very peculiar characteristics, considering their own legal nature. Accounting can guarantee asset control, efficiency, security and transparency in the provision of accounts for internal and external users of economic and financial information. In view of the above, this study was developed with the general objective of demonstrating the importance of Accounting in the provision of condominium accounts. Theoretical basis was sought in authors, standards and legislation. The research methodology was based on the researcher's experience of more than ten years and his knowledge of the legislation applied in the Condominiums segment, in addition to three qualitative interviews with experts on the subject. As a result, the opportunity was taken to develop an Accounting Manual for Condominiums. In a practical and objective way, this work is expected to provide guidance and adaptation to accounting practices in Residential Condominiums